The Quantity of Epicardial Adipose Tissue in Patients Having Ablation for Atrial Fibrillation With and Without Heart Failure - Wang Xu; Butcher Steele C.; Kuneman Jurrien H.; Lustosa Rodolfo P.; Fortuni Federico; Ajmone Marsan Nina; Knuuti Juhani; Bax Jeroen J.; Delgado Victoria (Elsevier Inc., 2022)
The distribution of epicardial adipose tissue (EAT) across the spectrum of heart failure (HF) has yet to be fully elucidated. The present study investigated the distribution of EAT in an HF spectrum and its association with clinical and echocardiographic parameters. A total of 326 patients who underwent contrast-enhanced computed tomography before transcatheter atrial fibrillation ablation with and without HF symptoms, and a wide range of left ventricular (LV) ejection fractions (LVEF) were included. EAT mass was quantified on contrast-enhanced computed tomography using dedicated software. A total of 36 patients had HF with reduced LVEF (HFrEF) (11.0%), 46 had HF with mid-range LVEF (HFmrEF) (14.1%), 53 had HFpEF (16.3%), and 191 did not have HF symptoms (58.6%) and were considered controls. Patients with HFpEF had the largest EAT mass, significantly higher than the control group (128 ± 36 g vs 95 ± 35 g, p <0.001), the HFmrEF group (101 ± 37 g, p <0.001), and the HFrEF group (103 ± 37 g, p = 0.002). However, there were no differences in EAT mass between patients with HFrEF, HFmrEF, and controls. EAT was independently associated with E/e', LV mass index, and tricuspid regurgitation velocity. Male gender, body mass index, and C-reactive protein levels were independently associated with EAT. In conclusion, patients with HFpEF had more EAT than patients with HFmrEF, patients with HFpEF, and controls. EAT was associated with worse LV diastolic dysfunction, whereas C-reactive protein levels were independently associated with EAT, suggesting an active inflammatory component.